Vestibular Schwannoma Tumor Size and Growth Rate Predict Response with Gamma Knife Stereotactic Radiosurgery - Killeen, Daniel E.; Tolisano, Anthony M.; Isaacson, Brandon; Kutz, J Walter; Barnett, Samuel; Wardak, Zabi; Hunter, Jacob B. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The aim of this study is to determine if pretreatment growth of sporadic vestibular schwannomas (VS) predicts postradiosurgery response.Methods This study was a retrospective chart review at a tertiary referral center of patients with VS that had at least two pretreatment magnetic resonance imaging (MRI) studies at least 6 months apart and underwent Gamma Knife radiosurgery with a minimum of 14 months postradiosurgery imaging surveillance. Tumor linear measurements and volumetric segmentation were assessed before and after radiosurgery. The main outcome measure was persistent enlargement following radiosurgery, defined as 2 mm enlargement in greatest axial diameter or 20% enlargement in volume without size regression.Results Thirty-five patients met the inclusion criteria. Patients were observed for median pre- and posttreatment intervals of 29.5 and 40.6 months, respectively. Median dose to the tumor margin was 13 Gy. Postradiosurgery enlargement occurred in six (17.1%) and nine (25.7%) patients based on linear and volumetric enlargement definitions, respectively. Pseudoprogression—defined as tumor enlargement—followed by linear or volumetric regression that occurred in 34.3% of tumors, reaching a maximum size at a median time of 6.3 months (3.3–8.4) postradiosurgery. When controlling for age, gender, and radiation dose, preradiosurgery tumor volume less than 0.3 cm3 (odds ratio [OR]: 59.7, p = 0.012) and preradiosurgery tumor diameter growth rate greater than or equal to 2.5 mm/year (OR: 19.3, p = 0.045) were associated with persistent postradiosurgery tumor enlargement.Conclusion Smaller pretreatment tumor volume and greater linear tumor growth rates were associated with postradiosurgery tumor enlargement when controlling for age, gender, and radiation dose.Level of Evidence This study indicates that the level of evidence is V.
Keywords: vestibular schwannoma; radiosurgery; radiation; Gamma Knife; volumetric analysis